2014
DOI: 10.1097/ccm.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Levels and Changes of High-Sensitivity Troponin T Are Associated With Cardiovascular Events in Vascular Surgery Patients*

Abstract: The risk predictive power of high-sensitive cardiac troponin T change in addition to the Revised Cardiac Risk Index could facilitate 1) detection of patients at highest risk for perioperative myocardial ischemia, 2) evaluation and development of cardioprotective therapeutic strategies, and 3) decisions for admission to and discharge from high-density care units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 32 publications
2
78
1
5
Order By: Relevance
“…These results differ from our study, which may be explained by the fact that they calculated postoperative troponin changes in relation to preoperative troponin levels, while we only studied postoperative troponin values. Furthermore, Gillmann and colleagues reported that absolute TnT changes were superior to relative TnT changes for perioperative risk prediction, which is in concordance with our finding that relative changes were not related to mortality [18].…”
Section: Literaturesupporting
confidence: 82%
See 1 more Smart Citation
“…These results differ from our study, which may be explained by the fact that they calculated postoperative troponin changes in relation to preoperative troponin levels, while we only studied postoperative troponin values. Furthermore, Gillmann and colleagues reported that absolute TnT changes were superior to relative TnT changes for perioperative risk prediction, which is in concordance with our finding that relative changes were not related to mortality [18].…”
Section: Literaturesupporting
confidence: 82%
“…They reported that half of the patients with postoperative troponin elevation had a relative change in TnT > 85% as compared to the preoperative TnT level, and one in four patients had a relative TnT change > 242%. Gillmann and colleagues studied both absolute and relative changes in patients undergoing vascular surgery, and found that an absolute change in TnT of as small as 6 ng/L, as compared to the preoperative TnT level, was independently associated with major adverse cardiac events, and that adding the TnT absolute change to clinical risk factors improved the predictive accuracy for major adverse cardiac events [18]. These results differ from our study, which may be explained by the fact that they calculated postoperative troponin changes in relation to preoperative troponin levels, while we only studied postoperative troponin values.…”
Section: Literaturementioning
confidence: 99%
“…Gillmann et al reported that a preoperative hs-cTnT ≥0.018 ng/mL and a perioperative increase in hs-cTnT ≥0.006 ng/mL were independently associated with major adverse cardiac events in vascular surgery patients. 24 Noordzij et al suggested that a relative change in hs-cTnT >50% from baseline value seemed to be appropriate for diagnosis of myocardial injury. 21 Eggers et al tested the best cutoff value to diagnose acute myocardial infarction among changes in hs-cTnT ≥20%, ≥50%, or ≥100% from baseline.…”
Section: Incidence Of Composite Of In-hospital Cardiovascular Eventsmentioning
confidence: 99%
“…23, 24 Eggers et al reported that the universal definition of acute myocardial infarction, together with ≥20% change in cardiac troponin I (cTnI) appears to improve the discrimination of acute from chronic causes of cTnI release. 25 The National Academy of Clinical Biochemists recommends that ≥20% change is indicative of Study Endpoints (Definition of PMI) The primary outcome was the incidence of PMI, but currently, there is no accepted definition of PMI.…”
Section: Study Protocolmentioning
confidence: 99%
“…A diagnosis of myocardial infarction requires larger changes and the presence of symptoms and/or changes in ECG. However, even small increases might be associated with major adverse cardiac events in the further course of the disease, as shown in a post-surgery study [14].…”
Section: Discussionmentioning
confidence: 99%